Efeito da Terapia Comunitária Integrativa sobre os sintomas de ansiedade e depressão em adolescentes - Alves, Mariane Inaraí (2020)
Adolescence is a period of intense changes at biological, psychological and social levels, which makes this phase more vulnerable to psycho-emotional changes, such as anxiety and depression. The aims of this study were to evaluate the effect of Integrative Community Therapy on the symptoms of depression and anxiety in adolescents and to evaluate the relationship of these comorbidities with non-suicidal self-injury. It is a quasi-experimental research, using a pre- and post-test evaluation. Participants consisted of 56 adolescents aged 12 to 17 years enrolled in a public school in southern Minas Gerais State, Brazil. The instruments for data collection were: Characterization of Participants, Economic Classification, Self-Injury Behavior Scale, Children’s Depression Inventory and Screen for Child Anxiety Related Emotional Disorders. There was a predominance of single female adolescents and the average age was 15 years old. About 32.1% of the total participants were in the first year of high school, 53.6% were economically classified in classes B2 and C1 and 42.9% lived with their parents. Most adolescents self-injured (87.5%) in the last year, reporting feeling little or no pain; 36.7% had suicidal ideation and 91.8% were not under the influence of alcohol or other drugs when they practiced self-injury. The most frequent age for the beginning of self-injury was 15 years, followed by 16 and 12 years. The most common types of self-injury were: picked at a wound, hit yourself on purpose and cut or carved on your skin. Among the reasons mentioned are: to relieve feeling numb or empty, to stop bad feelings and to get control of a situation. Of the 56 adolescents who participated of the study, 43 (76.8%) had anxious symptoms and 30 (53.6%) showed depression symptoms. A correlation between anxiety and depression was evidenced: as the anxiety score increases, the depression score also increases. The anxiety and depression scores are higher in those who performed self-injury. Girls had higher scores for anxiety, depression and higher rates of self-injurious behavior and were more likely to develop such comorbidities (anxiety O.R: 9.8, depression O.R: 4.2 and self-injury behavior O.R: 7.7). Adolescents who had suicidal ideation had higher scores for depression and higher frequency for self-injury, which was statistically significant. After the intervention with the Integrative Community Therapy, there was a statistically significant reduction in the anxiety and depression scores both for the total sample and for those who scored above the cutoff point. In a stratified analysis by gender, a significant reduction in anxiety and depression scores was observed only for females. However, for participants who scored above the cutoff point, only the depression variable for girls showed a statistically significant reduction. It was concluded that anxiety, depression and self-injury are problems reported by the adolescents of the study and these comorbidities are associated. The Integrative Community Therapy was an effective intervention in decreasing the scores of depression and anxiety; therefore, it was an effective tool of support and prevention of psycho-emotional suffering, being a concrete strategy with beneficial effects to the nurses' performance in the mental health care of adolescents in school context.